Design and development of grid independent integrated energy system for electric vehicle charging stations at different locations in Malaysia - Khan F.A.; Mekhilef S.; Ramachandaramurthy V.K.; Ab Aziz N.F.; Pal N.; Yaseen A.; Yadav A.; Asim M.; Alshammari O. (Elsevier Ltd, 2025)
Electric vehicles (EVs) have revolutionized the transportation sector as an alternative to conventional fossil fuel-based transportation. It becomes more effective when the charging energy comes from green, renewable, cost-effective, eco-friendly resources. The present work discusses modelling a hybrid renewable energy system for EV charging stations in Malaysia. This work presents techno-economic investigation for different hybrid energy system arrangements of solar photovoltaic (PV), wind turbine (WT), natural gas generator (GS) and battery energy storage (BES) for EV charging station. The EV load demand is calculated based on the transportation fleet of an institution considered for five different climatic locations in Malaysia using HOMER-Pro software. Considering the technical sizing of the hybrid system, the minimization of the energy system and net present cost are discussed for each locations. The optimization study of hybrid energy systems is further examined for social benefits and environmental analysis by including the human development and employment creation index. The comparative analysis of hybrid energy storage systems is performed separately. This study uses sensitivity analysis to elaborate on the cost-effectiveness and technical feasibility of the hybrid system, considering the cost of system components, macroeconomics parameters, and load variation. The finalized results indicate that the solar PV-BES-GS12 hybrid energy system is the most suitable combination for the integrated grid-independent EV charging station operation at each locations. ? 2024 Elsevier Ltd